2006
DOI: 10.1158/1078-0432.ccr-06-1196
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography–Diagnosed Emphysema, Not Airway Obstruction, Is Associated with the Prognostic Outcome of Early-Stage Lung Cancer

Abstract: Purpose: Because both emphysema and lung cancer can arise from biological damage caused by cigarette smoking, we investigated if the development of emphysema is associated with the clinical features of smoker's lung cancer. Experimental Design: The subjects were a consecutive series of 100 smokers who underwent lobectomy with hilar and mediastinal dissection for clinical stage I non^small cell lung cancer. We studied the relationship between the presence or absence of emphysema at the onset of the lung cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 34 publications
6
87
0
Order By: Relevance
“…This finding is consistent with previous studies, which also found COPD had no prognostic impact in patients with earlystage NSCLC or in patients with advanced NSCLC that received chemotherapy (10,19). In addition, the severity of emphysema in the present study was not well correlated with FEV 1 (%), which was also reported by Ueda et al (10).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is consistent with previous studies, which also found COPD had no prognostic impact in patients with earlystage NSCLC or in patients with advanced NSCLC that received chemotherapy (10,19). In addition, the severity of emphysema in the present study was not well correlated with FEV 1 (%), which was also reported by Ueda et al (10).…”
Section: Discussionsupporting
confidence: 93%
“…Scores of the six regions were summed to obtain total scores, giving a minimum total score of 0 and a maximum of 24. Total CT-emphysema scores of 0 or 1 were defined as no emphysema, since 95% of nonsmokers in previous series had lungs with <5% emphysematous involvement (10).…”
Section: Ct-emphysema Scorementioning
confidence: 99%
See 1 more Smart Citation
“…The airway obstruction and treatment response of lung cancer is controversial. In early-stage lung cancer, emphysema, not airway obstruction, is associated with poor prognostic outcomes (9). But, the combination of COPD and cancer stage, age, gender and tumor grade improves the prediction of treatment response in NSCLC (10).…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of cumulative smoking dose, patients with chronic airflow obstruction have a greater risk for lung cancer (18,19). In recent studies addressing the association between emphysema and lung cancer, the presence of emphysema detected using chest computed tomography (CT) in smokers is reported to be an important risk factor for lung cancer and poor prognosis (20)(21)(22)(23)(24)(25). Thus, we hypothesized that genetic abnormality, including driver mutations, in lung cancer may differ according to the presence or absence of emphysema even in patients with the same histological type of cancer.…”
mentioning
confidence: 99%